Zinc oxide interface modification method and perovskite photoelectric device preparation method using zinc oxide interface modification method

By spin-coating an interface modification layer of ultra-thin alcohol polymer or polyethylene material on the ZnO transport layer, the performance attenuation problem caused by the direct contact between ZnO and perovskite is solved, and the stability and performance of perovskite optoelectronic devices are significantly improved.

CN119584828AInactive Publication Date: 2025-03-07NANJING TECH UNIV

Patent Information

Application Number
CN202411781254.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In perovskite optoelectronic devices, the direct contact between the ZnO electron transport layer and the perovskite luminescent layer will lead to irreversible chemical reactions, resulting in attenuation of device performance. Existing interface modification materials such as PEI and PEIE are not suitable for the ZnO/perovskite interface.

Method used

The ZnO transport layer is modified with ultra-thin alcohol polymer, polyvinylpyrrolidone or polyvinyl carbazole solution to form a modified layer of 0.1 to 1 nanometer thick to indirectly isolate the direct contact between perovskite and ZnO.

Benefits of technology

It significantly improves the operating stability of perovskite optoelectronic devices, reduces the potential barrier between the electron transport layer and the perovskite layer, and promotes good crystal growth and defect control of perovskite films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119584828A_ABST
    Figure CN119584828A_ABST
Patent Text Reader

Abstract

The invention provides an interface modification method of zinc oxide and a perovskite photoelectric device preparation method using the same, and belongs to the field of perovskite materials. According to the invention, the surface of the zinc oxide (ZnO) layer is spin-coated with an alcohol polymer, a polyvinylpyrrolidone solution or a polyvinyl carbazole solution, and annealing is carried out to form an ultrathin modification layer, so that interface modification of the ZnO transmission layer is realized; the interface modification layer used in the invention can reduce the potential barrier between the electron transport layer and the perovskite layer, and helps perovskite to form a light-emitting layer film with low defect density and good surface appearance; in addition, the operation stability of a perovskite light-emitting diode device can be remarkably improved through the perovskite thin film modified by the ZnO interface of the light-emitting layer of the perovskite photoelectric device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of perovskite materials, and in particular relates to a method for modifying the interface of zinc oxide and a method for preparing a perovskite photoelectric device using the same. Background Art

[0002] Lighting and display technology plays a huge role in people's work and life, and therefore has always attracted the attention of scientific researchers. Inorganic LEDs based on III-IV compounds have the disadvantages of high cost, insufficient resolution, and difficult color control, so traditional inorganic LEDs are gradually replaced by organic light-emitting diodes (OLEDs). OLEDs have high efficiency, continuously adjustable spectrum, and thin and bendable device materials, but they have low carrier mobility, limited brightness, narrow luminous color gamut, and difficulty in achieving efficient luminescence under high current. Therefore, there is an urgent need to find a luminescent material that can replace inorganic LEDs and OLEDs that is cheap, efficient, simple to prepare, and has excellent performance.

[0003] Metal halide perovskite materials have excellent optoelectronic properties such as continuously adjustable emission wavelength, high fluorescence quantum efficiency (PLQE), high color purity, and wide color gamut. Perovskite light-emitting diodes (PeLEDs) with perovskite as the light-emitting layer have high efficiency, high brightness, high color purity, wide emission color gamut, simple preparation process, and low material cost. At present, the external quantum efficiency (EQE) of PeLED is close to that of OLED, which started research earlier, so PeLED is considered to be a feasible solution to replace OLED. However, the working stability and reliability of the device restrict the industrialization of PeLED.

[0004] ZnO electron transport materials are widely used in the field of optoelectronic devices. However, as an electron transport layer in PeLED, if it is in direct contact with the light-emitting layer, the light-emitting layer will undergo irreversible chemical reactions during the operation of PeLED, causing the performance of the LED device to decay. Therefore, a suitable interface modification layer can inhibit the above-mentioned adverse interface reactions and significantly improve the operating stability of PeLED. Currently, the commonly used interface modification materials PEI and PEIE for PeLED were first used in the field of organic optoelectronic devices and are not the most suitable for ZnO / perovskite interface modification. Therefore, the development of interface modification materials that are more suitable for the perovskite field is of great significance to improving the stability of PeLED. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for modifying the interface of zinc oxide, using an ultra-thin alcohol polymer, a polyvinyl pyrrolidone solution or a polyvinyl carbazole solution to modify the ZnO transport layer and prepare a perovskite photoelectric device. Inserting an intermediate layer in the transport layer and the light-emitting layer can directly isolate the direct contact between the perovskite and the ZnO. Suitable interface modification materials can reduce the barrier between the electron transport layer and the perovskite layer, help the perovskite film crystal growth, inhibit the formation of defects on the film, and more importantly, significantly improve the operating stability of the perovskite photoelectric device.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for modifying the interface of zinc oxide, the method comprising providing a modification layer on the upper surface of an electron transport layer;

[0008] The modification layer is a structure formed by dissolving alcohol polymer, polyvinyl pyrrolidone or polyvinyl carbazole in a solvent to prepare a solution, directly spin coating, and annealing, wherein the thickness of the modification layer is 0.1-1 nanometer.

[0009] Furthermore, the alcohol polymer is polyethylene glycol or polyvinyl alcohol; the concentration of the solution is 0.1-10 mg / mL, the spin coating speed is 1000-10000 rpm, and the spin coating time is 20-60 s; the annealing temperature is 40-400° C., and the annealing time is 5-120 min.

[0010] Furthermore, the solvent used in the polyethylene glycol solution and the polyvinyl pyrrolidone solution is isopropyl alcohol; the solvent used in the polyvinyl alcohol solution is dimethyl sulfoxide; and the solvent used in the polyvinyl carbazole solution is chlorobenzene.

[0011] As another specific embodiment of the present invention, the present invention also provides a perovskite photoelectric device, which is prepared using zinc oxide prepared by the above-mentioned interface modification method. Further, the perovskite photoelectric device includes applications in solar cells and semiconductors.

[0012] As another specific embodiment of the present invention, the present invention also provides a method for preparing a perovskite photoelectric device, the method comprising the following preparation steps:

[0013] S1. ITO glass pretreatment:

[0014] The etched ITO glass substrate is cleaned and dried, and then placed in a UV ozone apparatus for 5 to 40 minutes for use;

[0015] S2. Preparation of electron transport layer

[0016] The ZnO nanocrystal solution was spin-coated on the ITO glass substrate in S1, and the substrate was placed on a hot plate for annealing for a period of time to form a ZnO nanocrystal transport layer; after the annealing was completed, the substrate was cooled to room temperature and then transferred to a glove box in a nitrogen atmosphere for treatment to obtain sample 1;

[0017] S3. Preparation of modified layer

[0018] Using any of the above interface modification methods, a modification layer is formed on the surface of the ZnO nanocrystal of sample 1 to obtain sample 2;

[0019] S4. Preparation of perovskite layer

[0020] Lead iodide PbI2, formamidine iodide FAI and 3,6,9-trioxaundecane-1,11-diamine ODEA are dissolved in N,N-dimethylformamide DMF and stirred thoroughly to obtain a perovskite solution;

[0021] After sample 2 is cooled to room temperature, the synthesized perovskite solution is spin-coated on the modified layer at a certain rotation speed for a period of time, and then placed on a hot stage for annealing to obtain sample 3 of the perovskite layer;

[0022] S5. Preparation of hole transport layer

[0023] After sample 3 is cooled to room temperature, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)]TFB is dissolved in chlorobenzene to obtain a TFB solution, and the TFB solution is spin-coated on the perovskite layer to form a hole transport layer, thereby obtaining sample 4;

[0024] S6, Evaporation Electrode

[0025] Place the sample 4 in the mask and transfer it to the vacuum evaporator. Vapor-deposit 5-10 nm thick molybdenum oxide MoO on the top of the sample 4. X The perovskite photoelectric device is obtained by preparing a silver Ag or gold Au electrode with a thickness of 50 to 100 nm.

[0026] Furthermore, the preparation method of the ZnO nanocrystal solution in step S2 includes:

[0027] S21: dissolving Zn(AC)2·2H2O and tetramethylammonium hydroxide pentahydrate TMAH in a mixed solvent of DMSO, ethanol and water;

[0028] S22: After the solution in step S21 is fully stirred, the original solution is added to a centrifuge tube, and ethyl acetate is added, and the mixture is centrifuged to remove the lower precipitate;

[0029] S23: adding ethanol, ethanolamine and ethyl acetate to the lower precipitate taken in step S22, centrifuging with a centrifuge, and taking the lower precipitate;

[0030] S24: Add ethanol and ethanolamine to the lower precipitate obtained in step S23 to obtain a ZnO nanocrystal solution.

[0031] Furthermore, in S21, the mass ratio of Zn(AC)2·2H2O, TMAH and the mixed solvent is 1:0.5-2.0:10-100, and the volume ratio of the mixed solvent DMSO, ethanol and water is 1-5:1:0-1.

[0032] Furthermore, in S2, the annealing temperature is 120-180° C., the annealing time is 20-40 min, and the thickness of the ZnO nanocrystal transport layer film is 5-20 nm.

[0033] Furthermore, the molar ratio of PbI2, FAI and ODEA in S4 was 1:1-3:0.1-1, and the concentration range of PbI2 in DMF was 0.1-1.0 mol / L;

[0034] When the perovskite solution is spin-coated, the rotation speed is 2000-4000 rpm, the spin-coating time is 20-40 s, the hot stage annealing temperature is 100-200° C., and the time is 10-20 min.

[0035] Furthermore, the thickness of the hole transport layer in S5 is 10-100 nm, the concentration of the spin-coated solution is 10-20 mg / mL, and the spin-coating rotation speed is 1000-4000 rpm.

[0036] The beneficial technical effects of the present invention are:

[0037] The present invention provides a ZnO interface modification method and a perovskite photoelectric device using the method, as well as a preparation method, which have the following beneficial effects compared with the prior art:

[0038] (1) The interface modification material of the present invention can not only reduce the potential barrier between the electron transport layer and the perovskite layer, but also help the perovskite to form a perovskite light-emitting layer film with low defect density and good surface morphology.

[0039] (2) The perovskite film with ZnO interface modification in the light-emitting layer of the perovskite photoelectric device of the present invention can effectively improve the performance of the device such as operating stability.

[0040] (3) The interface modification method used in the present invention innovatively proposes to spin-coat an ultra-thin layer of alcohol polymer PEG or PVA solution, or polyvinyl pyrrolidone or polyvinyl carbazole solution on the surface of the ZnO film, abandoning the traditional PEI and PEIE modification materials. The process of this method is simple to operate and the device performance is significantly improved. The perovskite photoelectric device prepared based on this method has the potential for commercial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 A diagram showing the structure of a perovskite photoelectric device prepared in an embodiment of the present invention;

[0042] Figure 2 Surface morphology of the perovskite films prepared in Example 1 of the present invention and Comparative Examples 1 to 3;

[0043] Figure 3 XRD curves of the perovskite films prepared in Example 1 and Comparative Examples 1 to 3 of the present invention;

[0044] Figure 4 The external quantum efficiency and current density curves of the perovskite photoelectric devices prepared in Example 1 and Comparative Example 2 of the present invention;

[0045] Figure 5 The current density and voltage, and the radiation brightness and voltage curves of the perovskite photoelectric devices prepared in Example 1 and Comparative Example 2 of the present invention are shown;

[0046] Figure 6 The external quantum efficiency and current density curves of the perovskite photoelectric devices prepared in Example 2 of the present invention and Comparative Example 2 are shown;

[0047] Figure 7 The current density and voltage, and the radiation brightness and voltage curves of the perovskite photoelectric devices prepared in Example 2 of the present invention and Comparative Example 2 are shown;

[0048] Figure 8 The external quantum efficiency and current density curves of the perovskite photoelectric devices prepared in Example 3 of the present invention and Comparative Example 2 are shown;

[0049] Fig. 9 The current density and voltage, and the radiation brightness and voltage curves of the perovskite photoelectric devices prepared in Example 3 of the present invention and Comparative Example 2 are shown;

[0050] Fig.10 The external quantum efficiency and current density curves of the perovskite photoelectric devices prepared in Example 4 of the present invention and Comparative Example 2 are shown;

[0051] Fig.11 The graphs are current density and voltage, and radiation brightness and voltage of the perovskite photoelectric devices prepared in Example 4 of the present invention and Comparative Example 2.

[0052] The diagram shows: ITO glass substrate 1, ZnO nanocrystal transport layer 2, modification layer 3, perovskite layer 4, hole transport layer 5, molybdenum oxide electrode 6, Ag or AU electrode 7. DETAILED DESCRIPTION

[0053] In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples. The following examples are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0054] See Figure 1 As shown, the perovskite photoelectric device of the present invention comprises, from bottom to top, an ITO glass substrate 1, a ZnO nanocrystal transport layer 2, a modification layer 3, a perovskite layer 4, a hole transport layer 5, a molybdenum oxide electrode 6, and an Ag or AU electrode 7.

[0055] Preferably, the modification layer in the present invention is formed by spin coating an alcohol polymer, a polyvinyl pyrrolidone (PVP) solution or a polyvinyl carbazole (PVK) solution on the surface of the ZnO electron transport layer and annealing to form an ultra-thin modification layer. Preferably, the alcohol polymer is a polyethylene glycol (PEG) solution or a polyvinyl alcohol (PVA) solution, wherein the solvent in the present invention is isopropanol, dimethyl sulfoxide or chlorobenzene.

[0056] As a specific embodiment of the present invention, the solvent used for the polyethylene glycol solution and the polyvinyl pyrrolidone solution is isopropyl alcohol; the solvent used for the polyvinyl alcohol solution is dimethyl sulfoxide; the solvent used for the polyvinyl carbazole, preferably poly (N-vinyl carbazole) solution is chlorobenzene.

[0057] In order to help perovskite form a perovskite light-emitting layer film with low defect density and good surface morphology, in the present invention, the concentration of the PEG, PVA, PVP and PVK solution is preferably 0.1-10 mg / mL.

[0058] When the ZnO film surface is spin-coated, a spin coater can be used for spin coating, wherein the alcohol polymer, polyvinyl pyrrolidone solution or polyvinyl carbazole solution is spin-coated at a speed of 1000 to 10000 rpm and the spin coating time is 20 to 60 seconds.

[0059] Furthermore, the annealing temperature of the alcohol polymer, polyvinyl pyrrolidone solution or polyvinyl carbazole solution after spin coating is 40-400° C., and the annealing time is 5-120 min.

[0060] The present invention also provides a method for preparing a perovskite photoelectric device, and the specific preparation steps are:

[0061] S1. ITO glass substrate pretreatment

[0062] The etched ITO glass substrate is cleaned and blown dry, and then placed in a UV ozone apparatus for treatment for 5 to 40 minutes for use.

[0063] S2. Preparation of electron transport layer

[0064] The ZnO nanocrystal solution was spin-coated on the ITO glass substrate in S1 and annealed on a hot stage at 120-180°C for 20-40 min to form a ZnO nanocrystal transport layer with a thickness of 5-20 nm. The annealing temperature was 120-180°C and the annealing time was 20-40 min. After the annealing was completed, the sample was cooled to room temperature and then transferred to a glove box in a nitrogen atmosphere for treatment to obtain sample 1.

[0065] S3. Preparation of modified layer

[0066] After dissolving an alcohol polymer, polyvinyl pyrrolidone or polyvinyl carbazole in a solvent to form a solution, the solution is directly spin-coated on the surface of the ZnO nanocrystal transport layer of sample 1, and annealed to form a modified layer; sample 2 is obtained; wherein the thickness of the modified layer is 0.1 to 1 nanometer, the concentration of the solution is 0.1 to 10 mg / mL, the spin-coating speed is 1000 to 10000 rpm, and the spin-coating time is 20 to 60 seconds; the annealing temperature is 40 to 400°C, and the annealing time is 5 to 120 minutes.

[0067] S4. Preparation of perovskite layer

[0068] Lead iodide PbI2, formamidine iodide FAI and 3,6,9-trioxaundecane-1,11-diamine ODEA are dissolved in N,N-dimethylformamide DMF and stirred thoroughly to obtain a perovskite solution; wherein the molar ratio of PbI2, FAI and ODEA is 1:1-3:0.1-1, and the concentration range of PbI2 in DMF is 0.1-1.0 mol / L.

[0069] After sample 2 is cooled to room temperature, the synthesized perovskite solution is spin-coated on the modified layer at a rotation speed of 2000-4000 rpm for 20-40 seconds, and annealed on a hot plate at 100-200° C. for 10-20 minutes to obtain sample 3 of the perovskite layer.

[0070] S5. Preparation of hole transport layer

[0071] After sample 3 is cooled to room temperature, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)]TFB is dissolved in chlorobenzene to obtain a TFB solution, and the TFB solution is spin-coated on the perovskite layer to form a hole transport layer to obtain sample 4; wherein the thickness of the hole transport layer is 10 to 100 nm, the concentration of the spin-coated solution is 10 to 20 mg / mL, and the spin-coating rotation speed is 1000 to 4000 rpm.

[0072] S6, Evaporation Electrode

[0073] Place the sample 4 in the mask and transfer it to the vacuum evaporator. Vapor-deposit 5-10 nm thick molybdenum oxide MoO on the top of the sample 4. XThe perovskite photoelectric device is obtained by preparing a silver Ag or gold Au electrode with a thickness of 50 to 100 nm.

[0074] As a specific embodiment of the present invention,

[0075] The preparation method of the ZnO nanocrystal solution in step S2 comprises:

[0076] S21: dissolving Zn(AC)2·2H2O and tetramethylammonium hydroxide pentahydrate TMAH in a mixed solvent of DMSO, ethanol and water;

[0077] S22: After the solution in step S21 is fully stirred, the original solution is added to a centrifuge tube, and ethyl acetate is added, and the mixture is centrifuged to remove the lower precipitate;

[0078] S23: adding ethanol, ethanolamine and ethyl acetate to the lower precipitate taken in step S22, centrifuging with a centrifuge, and taking the lower precipitate;

[0079] S24: Add ethanol and ethanolamine to the lower precipitate obtained in step S23 to obtain a ZnO nanocrystal solution.

[0080] The preparation method of the perovskite photoelectric device of the present invention is described and introduced below through specific examples and comparative examples.

[0081] Example 1

[0082] An embodiment of the present invention provides a method for preparing a perovskite photoelectric device, comprising the following steps:

[0083] S1. Synthesis of ZnO nanocrystal solution: 335.9 mg Zn(AC)2·2H2O and 508.5 mg tetramethylammonium hydroxide pentahydrate (TMAH) were dissolved in 20 mL of a mixed solvent of DMSO, ethanol and water (volume ratio of 1-5:1:0-1); after sufficient stirring, 10 mL of the original solution was added to a centrifuge tube, 15 mL of ethyl acetate was added, and the mixture was centrifuged at 3000 rpm for 3 min, and the lower precipitate was removed; 2 mL of ethanol, 10 μL of ethanolamine and 8 mL of ethyl acetate were added, and the mixture was centrifuged at 3000 rpm for 3 min, and the lower precipitate was removed; finally, 4 mL of ethanol and 40 μL of ethanolamine were added to obtain a zinc oxide nanocrystal solution.

[0084] S2. Prepare a perovskite solution: dissolve 40 mg of lead iodide (PbI2), 29.8 mg of formamidine iodide (FAI) and 5 mg of 3,6,9-trioxaundecane-1,11-diamine (ODEA) in 667 μL of N,N-dimethylformamide (DMF) and stir thoroughly to obtain a perovskite solution.

[0085] S3. Preparation of ITO substrate: Take out the etched ITO glass, first clean the glass surface with detergent, then ultrasonically clean it with deionized water and ethanol for 20 minutes each, then blow it dry with an air gun, and place the ITO glass in a UV ozone device for 20 minutes.

[0086] S4. Preparation of ZnO nanocrystal electron transport layer film: spin-coat the ZnO nanocrystal solution synthesized in S1 on the ITO substrate at a speed of 4000 rpm for 30 seconds, place it on a hot plate at 150°C for annealing for 30 minutes; after cooling to room temperature, transfer the sample to a glove box in a nitrogen atmosphere for further processing;

[0087] S5, spin coating modification layer, perovskite layer, hole transport layer: spin coat the PEG solution (0.5-1.5 mg dissolved in 1 mL isopropanol) on the ZnO layer at a speed of 5000 rpm for 30 seconds, place it on a hot stage at 100°C for annealing for 10 minutes to form a modification layer; after cooling to room temperature, spin coat the perovskite solution synthesized in S2 on the modification layer at a speed of 3000 rpm for 30 seconds, place it on a hot stage at 100°C for annealing for 14 minutes to form a perovskite layer; after cooling to room temperature, spin coat the TFB solution (15 mg dissolved in 1 mL chlorobenzene) on the perovskite layer at a speed of 2000 rpm to form a hole transport layer;

[0088] S6. Evaporation electrode: Place the sample in the mask and transfer it to the vacuum evaporator. Evaporate 7nm thick molybdenum oxide and 80nm thick Ag electrode on the top of the sample.

[0089] Example 2

[0090] The method for preparing a perovskite photoelectric device provided in an embodiment of the present invention is the same as that in Example 1, except that in step S3, the modification layer spin-coated on the ZnO layer is a PVA solution (0.5-2.0 mg dissolved in 1 mL of dimethyl sulfoxide), and the rest of the processes are the same as those in Example 1.

[0091] Example 3

[0092] The method for preparing a perovskite photoelectric device provided in an embodiment of the present invention is the same as that in Example 1, except that in step S3, the modification layer spin-coated on the ZnO layer is a PVP solution (0.5-2.0 mg dissolved in 1 mL of isopropanol), and the rest of the processes are the same as those in Example 1.

[0093] Example 4

[0094] The method for preparing a perovskite photoelectric device provided in an embodiment of the present invention is the same as that in Example 1, except that in step S3, the modification layer spin-coated on the ZnO layer is a PVK solution (0.5-2.0 mg dissolved in 1 mL of chlorobenzene), and the rest of the processes are the same as those in Example 1.

[0095] Comparative Example 1

[0096] The preparation method of the perovskite photoelectric device provided in this comparative example is the same as that in Example 1, except that in step S3, the modification layer is not spin-coated on the ZnO layer, and the rest of the processes are the same as those in Example 1.

[0097] Comparative Example 2

[0098] The preparation method of the perovskite photoelectric device provided in this comparative example is the same as that in Example 1, except that in step S3, the modification layer spin-coated on the ZnO layer is a polyethoxyethyleneimine (PEIE) solution (1.1 mg dissolved in 1 mL of isopropanol), and the rest of the processes are the same as those in Example 1.

[0099] Comparative Example 3

[0100] The preparation method of the perovskite photoelectric device provided in this comparative example is the same as that in Example 1, except that in step S3, the modification layer spin-coated on the ZnO layer is isopropyl alcohol (IPA), and the rest of the processes are the same as those in Example 1.

[0101] The device structures and performance test results of multiple embodiments and comparative examples of the present invention are as follows:

[0102] Figure 1 As shown in the structural diagram of perovskite optoelectronic devices, the LED device has an inverted structure.

[0103] Figure 2 The surface morphology of the perovskite film shows that the use of PEG to replace PEIE promotes the crystallization of the perovskite film and increases the grain size. The solvent IPA of PEG and PEIE has no significant effect on the morphology of the perovskite film. The use of PEG to modify the ZnO transport layer obtains a better grain structure, which has a strong innovative significance.

[0104] Figure 3 The XRD curve of the perovskite film shows that the perovskite film obtained by using PEG to modify ZnO has higher crystallinity and better (111) crystal plane orientation, which can significantly improve product performance.

[0105] Figure 4 External quantum efficiency and current density curve of perovskite photoelectric devices Figure 5 The current density and voltage, radiation brightness and voltage curves of the perovskite photoelectric device show that the device prepared by using PEG solution to modify ZnO has a maximum EQE of 20.33% and a maximum radiation brightness of 532W / m 2 / sr, 0.5-1.5 mg / mL PEG solution modified ZnO significantly improved the external quantum efficiency and radiation brightness of the obtained perovskite photoelectric devices, while effectively alleviating the current roll-off.

[0106] Figure 6 External quantum efficiency and current density curve of perovskite photoelectric devices Figure 7 The current density and voltage, radiation brightness and voltage curves of perovskite photoelectric devices show that the device prepared by using PVA solution to modify ZnO has a maximum EQE of 20.29% and a maximum radiation brightness of 532W / m 2 / sr, with excellent performance indicators.

[0107] Figure 8 External quantum efficiency and current density curve of perovskite photoelectric devices Fig. 9 The current density and voltage, radiation brightness and voltage curves of perovskite photoelectric devices show that the device prepared by using PVP solution to modify ZnO has a maximum EQE of 15.39% and a maximum radiation brightness of 429W / m 2 / sr, greatly improving key parameters such as radiation brightness.

[0108] Fig.10 External quantum efficiency and current density curve of perovskite photoelectric devices Fig.11 The current density and voltage, radiation brightness and voltage curves of perovskite photoelectric devices show that the device prepared by using PVK solution to modify ZnO has a maximum EQE of 13.12% and a maximum radiation brightness of 367W / m 2 / sr. Using PVK solution to modify the ZnO transport layer is a breakthrough attempt in the industry and has great commercial value.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for modifying the interface of zinc oxide, characterized in that: The method comprises providing a modification layer on the upper surface of the zinc oxide layer; The modification layer is a structure formed by dissolving alcohol polymer, polyvinyl pyrrolidone or polyvinyl carbazole in a solvent to prepare a solution, directly spin coating, and annealing; The thickness of the modified layer is 0.1 to 1 nanometer.

2. The interface modification method according to claim 1, characterized in that: The alcohol polymer is polyethylene glycol or polyvinyl alcohol; the concentration of the solution is 0.1-10 mg / mL, the spin coating speed is 1000-10000 rpm, and the spin coating time is 20-60 s; the annealing temperature is 40-400° C., and the annealing time is 5-120 min.

3. The interface modification method according to claim 2, characterized in that: The solvent used in the polyethylene glycol solution and the polyvinyl pyrrolidone solution is isopropanol; The solvent used in the polyvinyl alcohol solution is dimethyl sulfoxide; The solvent used for the polyvinyl carbazole solution is chlorobenzene.

4. A perovskite photoelectric device, characterized in that: The zinc oxide is prepared using the interface modification method described in any one of claims 1 to 3.

5. A method for preparing a perovskite photoelectric device, characterized in that: The method comprises the following preparation steps: S1. ITO glass substrate pretreatment The etched ITO glass substrate is cleaned and dried, and then placed in a UV ozone apparatus for 5 to 40 minutes for use; S2. Preparation of electron transport layer The ZnO nanocrystal solution was spin-coated on the ITO glass substrate in S1, and the substrate was placed on a hot plate for annealing for a period of time to form a ZnO nanocrystal transport layer; after the annealing was completed, the substrate was cooled to room temperature and then transferred to a glove box in a nitrogen atmosphere for treatment to obtain sample 1; S3. Preparation of modified layer Using the interface modification method described in any one of claims 1 to 3, a modification layer is formed on the surface of the ZnO nanocrystal of sample 1 to obtain sample 2; S4. Preparation of perovskite layer Lead iodide PbI2, formamidine iodide FAI and 3,6,9-trioxaundecane-1,11-diamine ODEA are dissolved in N,N-dimethylformamide DMF and stirred thoroughly to obtain a perovskite solution; After sample 2 is cooled to room temperature, the synthesized perovskite solution is spin-coated on the modified layer at a certain rotation speed for a period of time, and then placed on a hot stage for annealing to obtain sample 3 of the perovskite layer; S5. Preparation of hole transport layer After sample 3 is cooled to room temperature, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)]TFB is dissolved in chlorobenzene to obtain a TFB solution, and the TFB solution is spin-coated on the perovskite layer to form a hole transport layer, thereby obtaining sample 4; S6, Evaporation Electrode Sample 4 is placed in a mask and transferred to a vacuum evaporator. A molybdenum oxide electrode with a thickness of 5 to 10 nm and a silver Ag or gold Au electrode with a thickness of 50 to 100 nm are first and then evaporated on the top of sample 4 to obtain a finished perovskite photoelectric device.

6. The method for preparing a perovskite photoelectric device according to claim 5, characterized in that: The preparation method of the ZnO nanocrystal solution in step S2 comprises: S21: dissolving Zn(AC)2·2H2O and tetramethylammonium hydroxide pentahydrate TMAH in a mixed solvent of DMSO, ethanol and water; S22: After the solution in step S21 is fully stirred, the original solution is added to a centrifuge tube, and ethyl acetate is added, and the mixture is centrifuged to remove the lower precipitate; S23: adding ethanol, ethanolamine and ethyl acetate to the lower precipitate taken in step S22, centrifuging with a centrifuge, and taking the lower precipitate; S24: Add ethanol and ethanolamine to the lower precipitate obtained in step S23 to obtain a ZnO nanocrystal solution.

7. The method for preparing a perovskite photoelectric device according to claim 6, characterized in that: The mass ratio of Zn(AC)2·2H2O, TMAH and the mixed solvent in S21 is 1:0.5~2.0:10~100, and the volume ratio of the mixed solvent DMSO, ethanol and water is 1~5:1:0~1.

8. The method for preparing a perovskite photoelectric device according to claim 5 or 6, characterized in that: In S2, the annealing temperature is 120-180° C., the annealing time is 20-40 min, and the thickness of the ZnO nanocrystal transport layer film is 5-20 nm.

9. The method for preparing a perovskite photoelectric device according to claim 5, characterized in that: The molar ratio of PbI2, FAI and ODEA in S4 is 1:1-3:0.1-1, and the concentration range of PbI2 in DMF is 0.1-1.0 mol / L; When the perovskite solution is spin-coated, the rotation speed is 2000-4000 rpm, the spin-coating time is 20-40 s, the hot stage annealing temperature is 100-200° C., and the time is 10-20 min.

10. The method for preparing a perovskite photoelectric device according to claim 5, characterized in that: The thickness of the hole transport layer in S5 is 10-100 nm, the concentration of the spin-coated solution is 10-20 mg / mL, and the spin-coating rotation speed is 1000-4000 rpm.

Citation Information

Patent Citations

  • Preparation method for ZnO nanocrystalline thin-film transistor type UV detector

    CN105655442A

  • Inorganic perovskite light emitting diode and preparation method thereof

    CN108511633A

  • Perovskite material, perovskite thin film, optoelectronic device and preparation method thereof

    CN116396174A

  • Manufacturing method of flexible perovskite monocrystalline silicon laminated solar cell

    CN117062495A

Cited By

  • High-performance perovskite quantum dot light-emitting diode based on blending modification of carbazolyl phosphonic acid and derivatives thereof and preparation method of high-performance perovskite quantum dot light-emitting diode

    CN122318494A